(NsRAWNITELXNO(B-(NSEMASIOLOGI^ESKIE ISSLEDOWANIQ (B:s ((NrOMANSKIE QZYKI(B) /s - d ((NmOSKWA (B:s (Nmgu(B,s, 1963)
(NbIBILIOGR(B.: (NS(B. 276 - 288s
Keywords: (NrOMANSKIE QZYKI (B- (NsEMANTIKAs; (NsRAWNITELXNO(B-(NISTORI^ESKOE IZU^ENIEs